2019 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR) 2019
DOI: 10.1109/cvpr.2019.00116
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the Envelope for RGB-Based Dense 3D Hand Pose Estimation via Neural Rendering

Abstract: Estimating 3D hand meshes from single RGB images is challenging, due to intrinsic 2D-3D mapping ambiguities and limited training data. We adopt a compact parametric 3D hand model that represents deformable and articulated hand meshes. To achieve the model fitting to RGB images, we investigate and contribute in three ways: 1) Neural rendering: inspired by recent work on human body, our hand mesh estimator (HME) is implemented by a neural network and a differentiable renderer, supervised by 2D segmentation masks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
176
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(178 citation statements)
references
References 63 publications
(179 reference statements)
2
176
0
Order By: Relevance
“…Baek et al [119] proposed a model that is able to estimate the 3D skeleton structure of the hand from the RGB image and recover the hand shape from it. In their work, a 2D skeleton model was used to predict 21 joint points, and the 3D hand model used a generative mesh model named MANO [120] representing the hand grid based on 45-dimensional pose parameters and 10-dimensional shape parameters, which was used in some very recent work [121,122].…”
Section: Hybrid Methodsmentioning
confidence: 99%
“…Baek et al [119] proposed a model that is able to estimate the 3D skeleton structure of the hand from the RGB image and recover the hand shape from it. In their work, a 2D skeleton model was used to predict 21 joint points, and the 3D hand model used a generative mesh model named MANO [120] representing the hand grid based on 45-dimensional pose parameters and 10-dimensional shape parameters, which was used in some very recent work [121,122].…”
Section: Hybrid Methodsmentioning
confidence: 99%
“…Baek et al [126] proposed a method that leverages the MANO hand model with 3D supervision, as well as hand segmentation masks and 2D supervision, to train a hand pose estimation CNN. Their network took an RGB image as input, estimated the 2D joint positions, and used them along with the image feature vector to predict the camera and the hand model parameters.…”
Section: Model-based Approachesmentioning
confidence: 99%
“…Iqbal [116] 0.710 AUC Dexter+Object [141] Multimodal Unimodal Inference Zhou et al [135] 0.948 AUC He et al [127] 12.40 mEPE Baek et al [126] 0.926 AUC Model-based Zhang et al [124] 0.901 AUC Iqbal et al [116] 13.41mEPE/0.940 AUC Theodoridis et al [118] 15.61 mEPE/0.907 AUC…”
Section: Model-freementioning
confidence: 99%
See 1 more Smart Citation
“…Hand pose estimation has been a major research area in the computer vision field, and it has benefited considerably from the rise of deep learning. Especially, hand pose estimation using a single color image as DeepFisheye, is an active re search area [3,47,63,72,78,82]. Zimmermann et al [81] suggested a deep learning pipeline that segments a hand in an image, identifies keypoints, and finally estimates the most likely hand pose.…”
Section: D Hand Pose Estimation Using a Cameramentioning
confidence: 99%